Improving Access to Thrombolysis and Inhospital Management Times in Ischemic Stroke: A Stepped-Wedge Randomized Trial. Issue 2 (February 2018) - Haesebaert, Julie; Nighoghossian, Norbert; Mercier, Catherine; Termoz, Anne; Porthault, Sylvie; Derex, Laurent; Gueugniaud, Pierre-Yves; Bravant, Estelle; Rabilloud, Muriel; Schott, Anne-Marie; Saligari, Elisabeth; Cailler, Samira; et al.
Abstract : Background and Purpose—: A suboptimal number of ischemic stroke patients eligible for thrombolysis actually receive it, partly because of extended inhospital delays. We developed a comprehensive program designed for emergency unit staff and evaluated its effectiveness for reducing intrahospital times and improving access to thrombolysis. Methods—: We conducted a randomized stepped-wedge controlled trial in 18 emergency unit. The sequentially implemented training intervention, targeting emergency physicians and nurses, was based on specifically designed videos and interactive simulation workshops on intrahospital management optimization. The effectiveness was assessed on intrahospital times and thrombolysis proportion. During the study period, all consecutive patients with confirmed ischemic stroke and no contraindications to thrombolysis were included. Results—: A total of 328 patients were enrolled in the control group and 363 in the intervention group. Mean age was 73.6 years. Overall thrombolysis proportion was 34.2% in the intervention group versus 25.6% in the control group (adjusted odds ratio, 1.42; 95% confidence interval, 1.01–2.01), thrombolysis proportion within 4 hours 30 minutes almost doubled (adjusted odds ratio, 1.9; 95% confidence interval, 1.32–2.73). Although imaging-to-stroke unit time was significantly decreased in the intervention group (39 versus 53 minutes; P =0.03), median door-to-imaging and door-to-needle times were not different between groups ( P =0.70 and P =0.40, respectively). Conclusions—: An interactive and multifaceted training program targeting emergency professionals was significantly associated with an increased access to thrombolysis, especially within 4 hours and 30 minutes. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02814760. Abstract : Supplemental Digital Content is available in the text.